2015
DOI: 10.1002/app.42580
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐induced crystallization behavior of phenolic resin crosslinked natural rubber/clay nanocomposites

Abstract: Nanocomposites of natural rubber (NR) and unmodified clay were prepared by latex compounding method. Phenolic resin (PhOH) was used to crosslink NR. Crosslinked neat NR was also prepared for comparison. The structure–property relationship of uncrosslinked and crosslinked NR/clay nanocomposites was examined to verify the reinforcement mechanism. Microstructure of NR/clay nanocomposites was studied by using transmission electron microscopic (TEM), X‐ray diffraction (XRD), wide angle X‐ray diffraction (WAXD), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 30 publications
(60 reference statements)
4
28
0
Order By: Relevance
“…On the other hand, the WAXD images of the PhOH‐NR and PhOH‐NRNCs containing 1 and 3 phr clay did not show the reflection spots and their WAXD patterns still showed an amorphous halo at strain of 200%. For the neat NR crosslinked with 10 phr PhOH, it was found that the crystallization occurred at the strain level approximately about 300%, while the crystallization was developed at much lower strain of about 100% in the NR nanocomposite with 5 phr clay crosslinked with the same amount of PhOH because of faster NR chain alignment in the presence of clay . It is also interesting to see that the intensities of crystalline peaks at the strain of 200% [Figure (B)] appeared to increase with increasing clay loading from 5 to 10 phr, indicating an increased NR chain alignment.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…On the other hand, the WAXD images of the PhOH‐NR and PhOH‐NRNCs containing 1 and 3 phr clay did not show the reflection spots and their WAXD patterns still showed an amorphous halo at strain of 200%. For the neat NR crosslinked with 10 phr PhOH, it was found that the crystallization occurred at the strain level approximately about 300%, while the crystallization was developed at much lower strain of about 100% in the NR nanocomposite with 5 phr clay crosslinked with the same amount of PhOH because of faster NR chain alignment in the presence of clay . It is also interesting to see that the intensities of crystalline peaks at the strain of 200% [Figure (B)] appeared to increase with increasing clay loading from 5 to 10 phr, indicating an increased NR chain alignment.…”
Section: Resultsmentioning
confidence: 94%
“…According to WAXD patterns of the PhOH‐NR and PhOH‐NRNCs at different levels of strain, the degree of crystallinity (X c ) could be determined from the intensities of the (200) and (120) plane diffraction peaks . Figure shows the change of X c as a function of strain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Natural rubber (NR) is an elastomer with a basic monomer of cis‐1,4‐polyisporene and its stereoregularity contributes to the strain‐induced crystallization when stretching due to the ability of molecular chain arrangement along the stretching direction . NR can provide high tensile strength and resistance to cutting, tearing and abrasion, owing to the strain‐induced crystallization.…”
Section: Introductionmentioning
confidence: 99%